Galán and the people: deconstructing the hero, reconstructing the story. (The Voz a Vos Bulletin, 2022)
This article describes the process of creation and dramaturgical commitment of the plot woven around the events that surround the end and destiny of the community rebellion. Around the figure of José Antonio Galán and the commons: dissatisfied masses of marginalized men and women. It is intended to reflect in a detailed and sincere way the creative turning points that invoked the writing and shaped the three scenes that have been written so far.
Keywords: Dramaturgy, identity, hero